ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFIT DISTRIBUTION MANAGEMENT PADA BANK UMUM SYARIAH TAHUN 2012-2015 - Teuku Rifadil fadil; Said Muniruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study aims to analyze the factors affecting Profit Distribution Management at Sharia Commercial Bank in Indonesia. Dependent variable used in this research is Profit Distribution Management. Independent variables used in this study include capital adequacy, Financing Risk, effectiveness of third party funds, Bank age This study uses a sample of sharia banks registered in Bank Indonesia in the period 2012-2015. Data were collected using purposive sampling technique. The analysis test used is classical assumption test, hypothesis test, and multiple regression analysis test. The result of multiple linear regression test shows that the variable of Capital Adequacy, Financing Risk, has a significant positive effect on Profit Distribution Management. While the variable of Third Party Fund Effectiveness and Age of Bank have negative influence not significant to Profit Distribution Management. The result of this research is expected that management is better able to do product development based on the result that more in accordance with Islamic shariah